Histiocytic disorders of children and adults - Weitzman, Sheila; Egeler, Rudolph Maarten (Cambridge University Press, 2005)
This comprehensive reference on histiocytic disorders considers the genetics, pathophysiology, and clinical management of this wide range of diseases. It covers all aspects of hystiocytic disorders--from Langerhans cell histiocytosis and hemophagocytic lymphohistiocytosis, to the uncommon cutaneous and extracutaneous histiocytic disorders. Current views on the function of normal histiocytes in the immune system, the pathogenesis, underlying genetic defects, clinical presentation, treatment, controversies in therapy, salvage therapies and the late consequences are also presented.
Keywords: ANGIOM SKLEROTIZUJÍCÍ; Pediatrics; cytologie, klinická cytologie; pediatrie; histologie